Deconstructing Dravet syndrome neurocognitive development: A scoping review. (1st March 2021) - Bertuccelli, Margherita; Verheyen, Karen; Hallemans, Ann; Sander, Josemir W.; Ragona, Francesca; Bisiacchi, Patrizia; Masiero, Stefano; Del Felice, Alessandra
Abstract: Dravet syndrome (DS) is a rare severe epilepsy syndrome associated with slowed psychomotor development and behavioral disorders from the second year onward in a previously seemingly normal child. Among cognitive impairments, visuospatial, sensorimotor integration, and expressive language deficits are consistently reported. There have been independent hypotheses to deconstruct the typical cognitive development in DS (dorsal stream vulnerability, cerebellar‐like pattern, sensorimotor integration deficit), but an encompassing framework is still lacking. We performed a scoping review of existing evidence to map the current understanding of DS cognitive and behavioral developmental profiles and to summarize the evidence on suggested frameworks. We searched PubMed, Scopus, PsycInfo, and MEDLINE to identify reports focusing on cognitive deficits and/or behavioral abnormalities in DS published between 1978 and March 15, 2020. We followed the Preferred Reporting Items for Systematic reviews and Meta‐Analyses extension for Scoping Reviews (PRISMA‐ScR) guidelines. Twenty‐one reports were selected and tabulated by three independent reviewers based on predefined data extraction and eligibility forms. Eighteen reports provided assessments of global intelligence quotients with variable degrees of cognitive impairment. Eleven reports analyzed single subitems contribution to global cognitive scores: these reports showed consistently larger impairment in performance scales compared to verbal ones. Studies assessing specific cognitive functions demonstrated deterioration of early visual processing, fine and gross motor abilities, visuomotor and auditory‐motor integration, spatial processing, visuo‐attentive abilities, executive functions, and expressive language. Behavioral abnormalities, reported from 14 studies, highlighted autistic‐like traits and attention and hyperactivity disorders, slightly improving with age. The cognitive profile in DS and some behavioral and motor abnormalities may be enclosed within a unified theoretical framework of the three main hypotheses advanced: a pervasive sensorimotor integration deficit, encompassing an occipito‐parietofrontal circuit (dorsal stream) dysfunction and a coexistent cerebellar deficit.